The effect of healthy eating index-2015 in the associations of biological aging and non-alcoholic fatty liver disease: an interaction and mediation analysis - Xiang Zhang; Zhijie Ding; Yong Yan; Weiming Yang; Xiaoming Ai; Yongping Zhou (Journal of Health, Population and Nutrition)
Abstract Background The present study explored the association between biological aging (BA), healthy eating index-2015 (HEI-2015) and non-alcoholic fatty liver disease (NAFLD) in the general population of the United States. Methods We used data from the NHANES database between 2017–2018 years to conduct the study. Weighted multivariable logistic regression analysis, restricted cubic spline (RCS), and subgroup analysis were performed to analyze the association of BA and HEI-2015 with prevalence of NAFLD and the mediation effect of HEI-2015 was also discussed. Additionally, generalized additive model was conducted to investigate the association of BA and HEI-2015 with ZJU index, BARD score, and NAFLD fibrosis score. Results There was a total of 2,421 individuals. RCS shown that BA was positively correlated with prevalence of NAFLD, while HEI-2015 was negative correlated with NAFLD risk. After adjusting for interfering factors, compared with the lowest quartiles of BA and HEI-2015, the odds ratios with 95% confidence intervals for NAFLD across the quartiles were (1.24 (0.84, 1.84), 2.07 (1.15, 3.73) and 2.49 (1.16, 5.38)) and (0.89 (0.66, 1.18), 0.87 (0.65, 1.16) and 0.64 (0.46, 0.87)), respectively. The BA was linear positive with ZJU index, BARD score and NAFLD fibrosis score. However, the linear negative correlation existed between HEI-2015 and ZJU index, BARD score and NAFLD fibrosis score. Mediation analysis showed that the positive correlation between BA and NAFLD could be mediated and weakened by HEI-2015. Conclusions The prevalence of NAFLD gradually increases with BA, but this positive association can be weakened by the healthy diet.